2015
DOI: 10.17116/oftalma2015131432-37
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of hemodynamic disturbances in magistral vessels to optic neuropathy progression and ocular tension changes in endocrine ophthalmopathy

Abstract: Long-lasting chronic impairment of blood supply of the eyeball leads to reduction in ocular tension and progression of optic neuropathy. Combined perfusion disturbances in CRA and LPCA as well as in CRA, LPCA, and SPCA can be considered a high-risk factor, while SPCA and/or LPCA involvement--a moderate-risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
0
0
3
Order By: Relevance
“…Changes in orbital blood flow in patients with TED have been reported in previous studies ( 9 11 , 22 24 ). Using color Doppler sonography, Somer et al ( 23 ) reported lower mean superior ophthalmic vein blood flow velocity in patients with TED compared with those without TED.…”
Section: Discussionsupporting
confidence: 77%
“…Changes in orbital blood flow in patients with TED have been reported in previous studies ( 9 11 , 22 24 ). Using color Doppler sonography, Somer et al ( 23 ) reported lower mean superior ophthalmic vein blood flow velocity in patients with TED compared with those without TED.…”
Section: Discussionsupporting
confidence: 77%
“…При этом лишь единичные работы посвящены анализу кровотока в a. Ophthalmica, a. et v. Retinae centralis, a. Ciliaris posterior brevis et longae на фоне первичного нелеченого тиреотоксикоза и гипотиреоза. В представленных публикациях внимание исследователей сконцентрировано на доплерографических параметрах, характеризующих скоростные показатели кровотока, не отражающие в пол-ной мере глубину ишемии органа зрения, в частности, его переднего отдела [4,5]. Между тем именно ишемия преэкваториального отдела определяет гидродинамику глаза и чувствительность зрительного анализатора к любым патогенным механизмам, включая ишемический фактор [6].…”
Section: Ischemia Of the Eye On The Background Of Primaryunclassified
“…Собственно, это заключение подтверждают представленные выше показатели ПОКа, МОКа и МОКv. Результаты плетизмографии подтверждают, что даже при отсутствии эндокринной офтальмопатии у больных с ПГТ и ПТТ развиваются глубокие гемодинамические нарушения в магистральных сосудах глаза [5]. Это приводит к ишемии переднего и заднего отделов глаза, что может повлечь за собой гидродинамические нарушения, повысить чувствительность зрительного анализатора к ишемии и гипоксии и способствовать развитию вторичной оптической нейропатии.…”
Section: результаты и обсуждениеunclassified
“…Появились работы, свидетельствующие о по-вышении внутриглазного тонуса при тиреоидной дисфункции. Для объяснения этого факта одни авторы указывают на затруднение оттока водянистой влаги в трабекулярной сети [9][10][11], другие полагают, что повышается секреция водянистой влаги [9,12].…”
Section: Introductionunclassified